Scientific blunders : a brief history of how wrong scientists can sometimes be-- - Youngson, R. M. (New York : Carroll & Graf, 1998)
Describes cases where the brightest scientific minds reached wrong conclusions from the belief that the earth is flat to the cold fusion affair in the 1980s.
Star errors -- They laughed at Wegener -- The flat earth theory -- Getting the calendar wrong -- Why is the sky dark at night? -- Lord Kelvin's time-bomb fizzles out -- The CIA and UFOs -- The great Lamarck blunder -- Soapy Sam's defeat -- Who was G.W. Sleeper? -- Piltdown -- What killed the dinosaurs -- Hero and the prime mover -- A galvanic error -- Perpetual motion -- Which way is down? -- Newton got it wrong -- The great AC/DC blunder -- The heat fallacies -- The n-ray blunder -- The importance of ether -- Atomic notions -- The cold fusion affair -- Euclid got it wrong -- Any fool can use the differential calculus -- The destruction of Alan Turing -- The millennium date blunder -- The four elements -- The historical oxygen blunder -- A pathological modesty -- Alchemy's failure -- Isaac Newton, alchemist -- A martyr to chemistry -- Spermatic homunculi -- Wishful thinking of a biologist -- The protein gene blunder -- Francis Galton's great misconception -- The Lysenko blunder -- The wrong dogma -- The SV40 near miss -- Magnets for toothache -- The opium blunder -- The Charcot shaker and the Tourette trembler -- The syphilis scandal.
Includes bibliographical references (p. 327-330) and index.
Adult
Keywords: Errors, Scientific; Errors; Science